L'aspect politique et collectif - Leslie, Peter (Les Cahiers de droit, 1986)
The Director of the Institute for Intergovernmental Relations herein underscores the fact that neither the protection of human rights nor political sovereignty can fully ensure the rights of national or ethnic minorities. He points out to this effect that the doctrine of liberalism is deficient due to its superficial apprehension of the relationship between the individual and the collectivity. As for the principle of sovereignty, it too fails on the level of social theory. The author proposes as a solution to the problem of ethnic minorities various elements. First, he suggests federalism, but mainly the instigation of a new political formula as a complement to the Canadian Charter of Rights and Freedoms. The purpose of this formula would be to define and ensure the rights of ethnic minorities through the drafting of standards of conduct, partial self-goverment and the establishing of intergovernmental accords.